Myocarditis and intramural coronary vasculitis in polyarteritis nodosa: an unusual treatable form of heart failure - Chimenti, Cristina (ESC Heart Fail, 2020)
We describe an uncommon cardiac presentation of polyarteritis nodosa. A 68‐year‐old woman, with a history of fatigue, weight loss, and myalgia of the lower extremities, was admitted for congestive heart failure. Coronary arteries were normal. Endomyocardial biopsy showed active lymphocytic myocarditis with associated intramural small vessels necrotizing vasculitis. The overexpression of TLR‐4 and the negativity for myocardial viruses suggested an immune mediated mechanism of cardiac damage. These histologic findings associated to weight loss >4 kg not due to dieting or other factors, myalgias, and polyneuropathy, were consistent with the diagnosis of polyarteritis nodosa. Immunosuppressive treatment, consisting of cyclophosphamide and prednisolone, led to a significant improvement of cardiac function. Polyarteritis nodosa can be the cause of unexplained heart failure due to myocarditis and intramural vessels vasculitis. Its recognition is crucial to obtain a cardiac recovery with a tailored immunosuppressive treatment.